Rapid and Efficient NO2 Sensing Performance of TeO2 Nanowires - Yunkun Shen; Kaili Wang; Hao Liu; Liping Chen; Zhihan Jin; Shancheng Yan (Sensors, 2023)
Gas sensors play a pivotal role in environmental monitoring, with NO2 sensors standing out due to their exceptional selectivity and sensitivity. Yet, a prevalent challenge remains: the prolonged recovery time of many sensors, often spanning hundreds of seconds, compromises efficiency and undermines the precision of continuous detection. This paper introduces an efficient NO2 sensor using TeO2 nanowires, offering significantly reduced recovery times. The TeO2 nanowires, prepared through a straightforward thermal oxidation process, exhibit a unique yet smooth surface. The structural characterizations confirm the formation of pure-phase TeO2 after the anneal oxidation. TeO2 nanowires are extremely sensitive to NO2 gas, and the maximum response (defined as the ratio of resistance in the air to that under the target gas) to NO2 (10 ppm) is 1.559. In addition, TeO2 nanowire-based sensors can return to the initial state in about 6–7 s at 100 °C. The high sensitivity can be attributed to the length–diameter rate, which adsorbs more NO2 to facilitate the electron transfer. The fast recovery is due to the smooth surface without pores on TeO2 nanowires, which may release NO2 quickly after stopping the gas supply. The present approach for sensing TeO2 nanowires can be extended to other sensor systems as an efficient, accurate, and low-priced tactic to enhance sensor performance.